A new oncolytic Vacciniavirus augments antitumor immune responses to prevent tumor recurrence and metastasis after surgery. Issue 1 (26th March 2020) - Ahmed, Jahangir; Chard, Louisa S; Yuan, Ming; Wang, Jiwei; Howells, Anwen; Li, Yuenan; Li, Haoze; Zhang, Zhongxian; Lu, Shuangshuang; Gao, Dongling; Wang, Pengju; Chu, Yongchao; et al.
Abstract : Background: Local recurrence and remote metastasis are major challenges to overcome in order to improve the survival of patients with cancer after surgery. Oncolytic viruses are a particularly attractive option for prevention of postsurgical disease as they offer a non-toxic treatment option that can directly target residual tumor deposits and beneficially modulate the systemic immune environment that is suppressed post surgery and allows residual disease escape from control. Here, we report that a novel Vaccinia virus (VV), VVΔTKΔN1L (with deletion of both thymidine kinase (TK) and N1L genes) armed with interleukin 12 (IL-12), can prolong postoperative survival when used as a neoadjuvant treatment in different murine and hamster surgical models of cancer. Methods: A tumor-targeted replicating VV with deletion of TK gene and N1L gene (VVΔTKΔN1L) was created. This virus was armed rationally with IL-12. The effect of VVΔTKΔN1L and VVΔTKΔN1L-IL12 on modulation of the tumor microenvironment and induction of tumor-specific immunity as well the feasibility and safety as a neoadjuvant agent for preventing recurrence and metastasis after surgery were assessed in several clinically relevant models. Results: VVΔTKΔN1L can significantly prolong postoperative survival when used as a neoadjuvant treatment in three different surgery-induced metastatic models of cancer. Efficacy was critically dependent on elevation of circulating natural killer cells that was achieved by virus-induced cytokine production from cells infected with N1L-deleted, but not N1L-intact VV. This effect was further enhanced by arming VVΔTKΔN1L with IL-12, a potent antitumor cytokine. Five daily treatments with VVΔTKΔN1L-IL12 before surgery dramatically improved postsurgical survival. VVΔTKΔN1L armed with human IL-12 completely prevented tumor recurrence in surgical models of head and neck cancer in Syrian hamsters. Conclusions: These data provide a proof of concept for translation of the regime into clinical trials. VVΔTKΔN1L-IL12 is a promising agent for use as an adjuvant to surgical treatment of solid tumors.